Assessments of healthy lifestyle practices using fuzzy / Mohd Khairi Mohd Adnan - Mohd Adnan, Mohd Khairi (2012)
The changes in the health behaviour of most individual nowadays are showing a trend towards a less healthy lifestyle. There are low levels of awareness about their health states. Health experts now describe lifestyle as one of the most important factors affecting health. In fact, it is estimated that as many as seven of the ten leading causes of death could be reduced through common-sense changes in lifestyle. Lifestyle assessment or evaluate is the process of identifying behavioural risk factors particular to an individual with the intent to encourage behaviour change for the prevention of poor health outcomes in the future. Improving the health of people living requires an initial assessment of their health status. Various instruments exist to measure perceived health. One such instrument is simply a question that asks people to rate their health as poor, fair, good, very good, or excellent. Six categories of lifestyle behaviour has used in this research, there are cigarette smoking, alcohol and drugs, eating habits, exercise/fitness, stress control and last one is safety. As fuzzy method has high potential of reasoning capability, the purpose of this research study is to investigate and develop an assessment system using fuzzy which are able to rate the health lifestyle practices based on behaviour of those six categories by answering a few provided questionnaire related to health style.